A high-throughput screening and computation platform for identifying synthetic promoters with enhanced cell-state specificity (SPECS) - Ming-Ru Wu (Nature Portfolio, 2019)
Synthetic promoters can be superior to native ones but the design is challenging without knowledge of gene regulation. Here the authors develop a pipeline that allows for screening a synthetic promoter library to identify high performance promoters in potentially any given cell state of interest.